Cataloging modernization: from ISBD standards to automated systems at USARB (Confluenţe Bibliologice, 2026)
This article examines the activities of the Cataloging, Indexing, and Classiﬁcation Oﬃce, the evolution of cataloging processes within the library, and the technological transformations that have taken place over the past decades. The Scientiﬁc Library of "Alecu Russo” Bălți State University is no exception: the shift from traditional cataloging, based on the ISBD standard and printed cards, to automated cataloging using modern information systems has represented a critical step toward the digitalization of library services and the enhancement of information accessibility.
Keywords: electronic catalog; cataloging; databases; TINLIB software; Aleph software